The Design and Simulation of Improved and Multiplex Boost Converter - Xuanfeng Shangguan; Huimin Yang; Yongliang Wang; Benlong Shi (Institute of Advanced Engineering and Science, 2014)
In a MW-level and high-power wind power system, the level of current and voltage is easy to exceed the capacity of one switch device, so single boost converter has already can't meet the requirements of system. To solve this problem , for 1.2MW direct drive VSCF wind power system this paper designed a improved and multiplex boost converter , the over-voltage protection circuit branch is inserted into the circuit. The system state equation and control strategy are given, and the input current ripple is analyzed. Finally, in the Matlab environment, build the model of direct-drive wind power generation system to verify the feasibility of this circuit. The results show that: the system can run stably, has high efficiency, low ripple and has a good practical value. DOI : http://dx.doi.org/10.11591/telkomnika.v12i4.5002